Experimental and Numerical Study on Mechanical Properties and Deformation Behavior of Beishan Granite considering Heterogeneity - Wang, Z. H.; Tan, Y. L.; Li, S. M.; Wang, T. Z.; Wu, X. C. (Advances in Civil Engineering, 2021)
Disposal of high-level radioactive waste (HLW) deep underground is one of the most challenging research subjects in rock engineering. In China, Beishan granite is usually chosen as host rock for the construction of the HLW repository. In this study, mechanical tests are conducted on Beishan granite and the stress-strain state during the complete failure process is analyzed by numerical simulation. The results show that the tensile strength and uniaxial compressive strength of Beishan granite are 8.66 and 162.9 MPa, respectively. Dilatancy appears when the stress reaches about 81% of the peak strength. Heterogeneity is introduced by Weibull distribution in numerical simulation. With the increase of homogenization degree, the degraded elements are more easily to concentrate locally. Based on experimental and numerical simulation results, it is noticeable that the sample volume is basically in the state of compaction before reaching the peak strength. The elements are more likely to show expansion, and the splitting failure dominates the destroy mode when the confining pressure is relatively low. With increasing confining pressure, more and more degraded elements are concentrated in the shear band, which develops from the surface to the interior of the sample during loading. Therefore, the granite shows ductile mechanical response characteristics when the confining pressure is relatively high. The results are instructive for the construction of the repository.